Metacognitive and Metaemotional Training Strategies through the Nine-layer Pyramid Model of Emotional Intelligence - Athanasios Drigas (International Association of Online Engineering (IAOE), 2021)
Emotional intelligence constitutes an important 21st century skill that impacts positively several areas of everyday life. It contains competencies that enhance the ability of other significant skills for self-development. The main purpose of this study is to present the way we can develop and improve our emotional intelligence based on the pyramid model and its nine layers. To achieve this goal, the paper seeks to address the following question: What are the metacognitive and metaemotional skills and strategies that can play a key role in developing, enhancing and improving emotional intelligence?Extensive reference is made to the skills that involved in each layer and have been identified as necessary and should be cultivated by the individual leading gradually to the higher levels of self-actualization and transcendence. Furthermore, we suggest some strategies in each layer that work auxiliary and supportive for the cultivation of the specific skills.Metacognitive and metaemotional skills and strategies are necessary to conquer the levels of emotional intelligence and to apply in a variety of contexts with the aim of developing emotional intelligence and self-improvement.